2012
DOI: 10.1007/s11104-012-1230-7
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization-immobilization of sulphur in a soil during decomposition of plant residues of varied chemical composition and S content

Abstract: The recycling of plant residues can be an important source of available sulphate in soils. This study investigates the effects of soil sulphate availability on residue decomposition and the relationships between plant residue quality and S and C mineralizationA soil incubation experiment examined rapeseed straw mineralization after adding sulphate at rates of 20 and 50 mg S-SO4 kg(-1) soil in a loamy soil. Soils amended with wheat straw, tall fescue, mustard or beech leaf residues were incubated. Net C and S m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Although considered a loss from the pasture ecosystem, harvested DM may be considered a C storage mechanism relative to the atmosphere. By assuming a 43.3% C concentration for harvested DM (Bélanger et al, 1994; Niknahad‐Gharmakher et al, 2012; Sanaullah et al, 2014), 9.7, 12.1, and 22.5 Mg of DM C ha −1 were stored in the unamended control, low‐BL, and high‐BL treatments, respectively, during the 2‐yr period (Table 3). Annual amendments of BL increased DM C storage by 1.3 and 2.3 times that from the control for the low‐BL (241 kg N ha −1 ) and high‐BL (482 kg N ha −1 ) treatments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Although considered a loss from the pasture ecosystem, harvested DM may be considered a C storage mechanism relative to the atmosphere. By assuming a 43.3% C concentration for harvested DM (Bélanger et al, 1994; Niknahad‐Gharmakher et al, 2012; Sanaullah et al, 2014), 9.7, 12.1, and 22.5 Mg of DM C ha −1 were stored in the unamended control, low‐BL, and high‐BL treatments, respectively, during the 2‐yr period (Table 3). Annual amendments of BL increased DM C storage by 1.3 and 2.3 times that from the control for the low‐BL (241 kg N ha −1 ) and high‐BL (482 kg N ha −1 ) treatments, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of compost C mineralized ( C min , %) was estimated by (Chen et al, ) Cmin=[]Rhcompost0.5×()RhUREARhCONTRhCONT/Ccompost×100% where Rh compost , Rh UREA , and Rh CONT are the cumulative Rh (g C m −2 ) in the compost treatment, UREA, and CONT, respectively; 0.5 is the ratio of urea‐N application rate in the compost treatment to that of the UREA treatment; and C compost is the amount of organic C input by compost application. This calculation was based on the assumptions that the priming effect induced by OM addition on SOC decomposition is negligible (Johnson et al, ; Niknahad‐Gharmakher et al, ) and that Rh from SOC decomposition was assumed to respond proportionally to N rate at the range of 100–200 kg N ha −1 (Zhong et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to the calculation of the C:N ratio in plant debris, in order to determine the amount of nitrogen available to plants, it is necessary to determine the availability of sulfur on the basis of the C:S ratio. Niknahad-Gharmakher [68] observed that amino acids containing sulfur, such as methionine and cysteine, were very quickly degraded by soil microorganisms. Therefore, sulfur is rapidly released from plant debris that is applied to the soil.…”
Section: Microbiological Mineralization Of Crop Residuesmentioning
confidence: 99%